Rethinking Debt Strategies: How Profits, Women’s Representation, and Politics Shape Corporate Leverage - Pandito, Muhammad Tora Bhanu; Nurmasari, Nuraini Desty (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to investigate the influence of profitability, women’s representation on boards of commissioners and directors, and political connections on the financial leverage of manufacturing companies listed on the Indonesia Stock Exchange (IDX). Design/methodology/approach – This explanatory quantitative study analyzes panel data from 115 manufacturing companies listed on the IDX during the 2018–2022 period. The data were examined using the Common Effect Model with Stata MP 17. Findings – The results indicate that profitability has a significant negative effect on financial leverage. In contrast, women’s representation on boards of commissioners and directors and political connections have negative but statistically insignificant effects on financial leverage. Originality/value – This study contributes to corporate finance and corporate governance literature by examining the combined influence of financial performance, board gender diversity, and political connections on leverage decisions in Indonesia’s manufacturing sector, helping to address inconsistent findings in previous studies.